Modelling of sorption-enhanced steam methane reforming in a fixed bed reactor network integrated with fuel cell. (15th January 2018) - Diglio, Giuseppe; Hanak, Dawid P.; Bareschino, Piero; Pepe, Francesco; Montagnaro, Fabio; Manovic, Vasilije
Graphical abstract: Highlights: A fixed bed reactor network was evaluated for sorption-enhanced steam methane reforming. A high-purity H2 stream (92%) and a concentrated CO2 stream were obtained. The system is energy-self-sufficient with near-zero-CO2 emissions. Integration of the system with a fuel cell led to a 51% net global efficiency. Abstract: In this study sorption-enhanced steam methane reforming (SE-SMR) in fixed beds is investigated by means of 1D numerical modelling, and the model is validated with the data reported in the literature. Isothermal conditions (973 K) are considered, and the equilibrium between the carbonation and calcination stages is shifted by a pressure swing: 3.5 · 10 6 Pa and 1013 Pa, respectively. The results showed that under these operating conditions at least 8 reactors in parallel are required to continuously produce a high-purity stream of H2, and a separated stream of concentrated CO2 . The average H2 purity is 0.92, whilst the average H2 yield and selectivity are 2.9 molH2 molCH4 −1 and 90%, respectively. A thermodynamic analysis was performed, which highlighted that, by using a portion of the produced H2 (about 0.4 molH2 molCH4 −1 ), it is possible to fully cover heat and power demands of the process, making it completely energy self-sufficient. In the case when the proposed SE-SMR is integrated with a solid oxide fuel cell, net power generation at the scale of ∼950 kWel can be achieved with a net efficiency of the entire system of 51%, with the important feature that CO2 is concentrated.